A comparison of single-run pushover analysis techniques for seismic assessment of bridges. - Pinho, R.
Traditional pushover analysis is performed subjecting the structure to monotonically increasing lateral forces with invariant distribution until a target displacement is reached; both the force distribution and target displacement are hence based on the assumption that the response is controlled by a fundamental mode, that remains unchanged throughout. However, such invariant force distributions cannot account for the redistribution of inertia forces caused by structural yielding and the associated changes in the vibration properties, including the increase of higher-mode participation. In order to overcome such drawbacks, but still keep the simplicity of using single-run pushover analysis, as opposed to multiple-analyses schemes, adaptive pushover techniques have recently been proposed. In order to investigate the effectiveness of such new pushover schemes in assessing bridges subjected to seismic action, so far object of only limited scrutiny, an analytical parametric study, conducted on a suite of continuous multi-span bridges, is carried out. The study seems to show that, with respect to conventional pushover methods, these novel single-run approaches can lead to the attainment of improved predictions.
Keywords: Displacement based; Adaptive pushover; Seismic analysis; Bridges; DAP; FAP